Remdesivir for the treatment of coronavirus COVID-19: A meta-analysis of randomised controlled trials. (March 2021) - Enoki, Yuki; Igarashi, Yuki; Watabe, Yuki; Honma, Kyoka; Suzuki, Yuto; Hayashi, Yukitaka; Hiraoka, Kana; Taguchi, Kazuaki; Matsumoto, Kazuaki
Highlights: Remdesivir is proposed as a therapeutic for COVID-19 Clinical improvement after remdesivir was higher compared with placebo Remdesivir tended to reduce patient mortality rate, but this was not significant